Ending the reign of the Fraser Institute's school rankings - Raptis, Helen (Canadian Journal of Education/Revue canadienne de l'éducation, 2012)
The Fraser Institute Report Card of school rankings has won the hearts of parents and the press. For over a decade, the rankings have been particularly burdensome for low-ranking (usually low socio-economic status, high-poverty) schools when parents of high-achieving children move them to higher-ranking schools. In February 2010, after defending parents’ rights to access the rankings, Victoria’s Times-Colonist newspaper decided not to publish them. Using critical discourse analysis, this article explores the rankings’ long media reign and the Times-Colonist’s abrupt decision to stop publishing them. Discourse about the rankings is shaped by multiple factors including the relationship between the press and educators, as well as the nature of societal discourse— in particular, how powerful institutions create what Foucault calls “regimes of truth.”